A study of seroprevalence and rates of asymptomatic viremia of severe fever with thrombocytopenia syndrome virus among Chinese blood donors. Issue 5 (15th December 2014) - Zeng, Peibin; Ma, Lili; Gao, Zhan; Wang, Jingxing; Liu, Jing; Huang, Xianwei; Yang, Qizhi; Cao, Ruan; Wen, Xiuqiong; Zhu, Lili; Ma, Hongli; Yang, Zhendong; et al.
<x xml:space="preserve">Abstract</x> Background Severe fever with thrombocytopenia syndrome virus (SFTSV), an emerging tick‐borne pathogen that can cause fatal severe fever with thrombocytopenia syndrome, was first identified in China in 2009. Limited evidence suggests that SFTSV can be transmitted between humans via blood contact, raising concerns over transfusion safety. A study of donor samples from three Chinese blood centers was conducted to investigate the seroprevalence and rate of SFTSV viremia among Chinese blood donors. Study Design and Methods From April 16 to October 31, 2012, a total of 17, 208 plasma samples were collected from donors at Xinyang (located in an SFTSV‐endemic area), Mianyang, and Luoyang Blood Centers. Assessment of anti‐SFTSV total antibody was performed on all samples using enzyme‐linked immunosorbent assay. Repeat‐reactive samples were tested for SFTSV RNA using reverse transcription (RT)–real‐time polymerase chain reaction (PCR) assay with Taqman probes. In addition, 9960 of the Xinyang samples were tested in pools of 4 by the same PCR method and each of the samples in a reactive pool was tested individually. Results Donor seroreactivity rates were as follows: Xinyang, 0.54% (80/14, 752); Mianyang, 0.27% (3/1130); and Luoyang, 0.28% (3/1326). All seroreactive samples were negative on RT‐PCR single‐sample testing. Two RT‐PCR–reactive donor samples were identified, both with estimated viral load of less than 20 plaque‐forming units/mL. The RNA prevalence rate for SFTSV among donors in Xinyang was 0.02%. Conclusion This was the first multiregion study of SFTSV sero‐ and viral prevalence among Chinese blood donors. Viral prevalence was low and no seroreactive sample was viremic, suggesting a limited impact of SFTSV on blood safety in China.